66.4k views
4 votes
Find f(7). f(x)=x^2+9

Find b(-2)-a(12). a(x)=13x-2;b(x)=8x-14

User HolloW
by
5.5k points

2 Answers

4 votes

Answer:

f(7)=58

b(-2)-a(12)=-188

Explanation:

f(7)=(7)^2+9

49+9

f(7)= 58

b(-2)-a(12)=8(-2)-14-13(12)-2

-16-14-156-2

=-188

User Joebarbere
by
5.9k points
1 vote

Answer:

Explanation:

f(7). f(x)=x^2+9

Put x = 7 in the equation

f(7) = 7^2 + 9 =58

Find b(-2)-a(12)

b(-2)=8x-14= -16-14=-30

a(x)=13x-2

a(12) =13×12 -2= 154

b(-2)-a(12) = -30-154

= -124

User Marc Ruef
by
5.0k points